Divide the folĺwing p(x) by the polynomial g(x) and find the quotient and remainder in each of the following
![1) \: p(x) = {x}^{2} - 3 {x}^{2} + 5x - 3 \\ g(x) = {x}^{2} - 2 1) \: p(x) = {x}^{2} - 3 {x}^{2} + 5x - 3 \\ g(x) = {x}^{2} - 2](https://tex.z-dn.net/?f=1%29+%5C%3A+p%28x%29+%3D++%7Bx%7D%5E%7B2%7D++-+3+%7Bx%7D%5E%7B2%7D++%2B+5x+-+3+%5C%5C+g%28x%29+%3D++%7Bx%7D%5E%7B2%7D++-+2)
Answers
Answered by
1
Step-by-step explanation:
Hope it helps you.....
Attachments:
![](https://hi-static.z-dn.net/files/d2a/22d254aad9685a93e011a65ecd79a861.jpg)
Similar questions
Math,
6 months ago
Business Studies,
6 months ago
English,
6 months ago
World Languages,
1 year ago
Math,
1 year ago
Math,
1 year ago